Industrial Training Report: Perpustakaan Sultanah Nur Zahirah Universiti Malaysia Terengganu / Hanis Fatihah Junaidi - Junaidi, Hanis Fatihah (Faculty of Information Management, 2018)
Trainee did industrial training at Perpustakaan Sultanah Nur Zahirah (PSNZ), Universiti Malaysia Terengganu (UMT) for five month starting from 1st of February until 29th of June 2018. During the industrial training trainee must do training at all departments in the library. The industrial training report consists of four chapters. The first chapter is the introduction that contains background of organization and organization structure. The second chapter is about organizational information which include department structure and department function. Next, chapter three is about industrial training activity that includes training activities and special project throughout industrial training. Lastly, chapter four is about industrial training reflection where trainee needs to relate application of knowledge, skills, and experience in undertaking the task (knowledge gained), personal thoughts and opinion, lesson learnt and also limitation and recommendation during training.